2006
DOI: 10.1111/j.1748-5827.2006.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of dexmedetomidine and buprenorphine, butorphanol or diazepam for canine hip radiography

Abstract: Dexmedetomidine sedative protocols, particularly in combination with butorphanol and diazepam, can be used effectively and safely in dogs for radiographic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 11 publications
4
45
1
1
Order By: Relevance
“…Many literatures suggested that BTR has minimal cardiovascular and respiratory effects, but when administered with α2 agonists it increases their depressant effect on heart and respiratory rates (Trim, 1983, Ko, et al, 2000, Sinclair, 2003 also bradycardiac effects of α2 agonists and butorphanol appeared to be additive (Bartram et al 1994). We proved here in our study that the DTM have the same side effects of MDM and DXM when combined with BTR (Bartram, et al, 1994, Grimm et al, 2000, Ko, et al 2000, Leppanen et al, 2006, Salla et al, 2014, Puighibet et al, 2015, Lee et al, 2016, Tamura et al, 2016.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Many literatures suggested that BTR has minimal cardiovascular and respiratory effects, but when administered with α2 agonists it increases their depressant effect on heart and respiratory rates (Trim, 1983, Ko, et al, 2000, Sinclair, 2003 also bradycardiac effects of α2 agonists and butorphanol appeared to be additive (Bartram et al 1994). We proved here in our study that the DTM have the same side effects of MDM and DXM when combined with BTR (Bartram, et al, 1994, Grimm et al, 2000, Ko, et al 2000, Leppanen et al, 2006, Salla et al, 2014, Puighibet et al, 2015, Lee et al, 2016, Tamura et al, 2016.…”
Section: Resultssupporting
confidence: 67%
“…The common form of α2 agonist in pet clinics, medetomidine (MDM) showed similar effect when combined with BTR and the author's stated that MDM-BTR could be enough for sedation of dogs to perform various clinical procedures (Bartram et al 1994). The MDM and its dextro-isomer (dexmedetomidine) (DXM) also has been previously used in similar studies (Bartram et al, 1994, Grimm et al, 2000, Ko et al, 2000, Leppanen et al, 2006, Salla et al, 2014, Puighibet et al, 2015, Lee et al, 2016, Tamura et al, 2016. The same combination in other animal species also proved to be efficient for sedation and antinociception like in equine (Joubert et al, 1999, Abu-Ahmed, 2007 and in ruminant (Carroll et al, 1998, Lin andRiddell, 2003).…”
Section: Resultsmentioning
confidence: 98%
“…Such myorelaxation was also observed in a study with dogs, which compared the combination of dexmedetomidine and buprenorphine with butorphanol and diazepam 16 . In the present study, the reduction of EMG values was more prominent than that of BIS values.…”
Section: Body Temperaturementioning
confidence: 81%
“…To reduce the cardiovascular effects and keep or potentiate the sedative effects of alpha 2 agonists, several authors proposed the combination of these agents with other drugs (Leppänen et al, 2006;Monteiro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%